2013
DOI: 10.1093/database/bat013
|View full text |Cite
|
Sign up to set email alerts
|

curatedOvarianData: clinically annotated data for the ovarian cancer transcriptome

Abstract: This article introduces a manually curated data collection for gene expression meta-analysis of patients with ovarian cancer and software for reproducible preparation of similar databases. This resource provides uniformly prepared microarray data for 2970 patients from 23 studies with curated and documented clinical metadata. It allows users to efficiently identify studies and patient subgroups of interest for analysis and to perform meta-analysis immediately without the challenges posed by harmonizing heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
232
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(235 citation statements)
references
References 46 publications
3
232
0
Order By: Relevance
“…To determine the relationship between the expression of SLC6A12 and overall survival in patients with serous-type OC, we performed meta-analysis using curatedOvarianData, which includes more than 2000 expression profiles and clinical data from OC patients 10. The results of the meta-analysis showed that high expression of SLC6A12 was significantly associated with poor prognosis in serous-type OC patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the relationship between the expression of SLC6A12 and overall survival in patients with serous-type OC, we performed meta-analysis using curatedOvarianData, which includes more than 2000 expression profiles and clinical data from OC patients 10. The results of the meta-analysis showed that high expression of SLC6A12 was significantly associated with poor prognosis in serous-type OC patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The association between the expression level of SLC6A12 and prognosis in serous-type OC was validated using a recently developed meta-analysis package, curatedOvarianData,10 composed of 2066 expression profiles and clinical data of OC patients from 13 datasets including only serous OC. Cox proportional hazards model was used to determine hazard ratio (HR) for overall survival in each dataset, and univariate meta-analysis was performed using fixed effect model for combining HRs.…”
Section: Methodsmentioning
confidence: 99%
“…NUAK1 transcript expression was assessed in a cohort of 1,262 patients assembled from seven publicly available, ovarian cancer Affymetrix microarray data sets downloaded from the curatedOvarianData database (14) and an independent cohort of 174 HGSOC patients with Agilent gene expression data (8) (Table 1). Of the ovarian cancer patients with Affymetrix data, 802 also had PFS data.…”
Section: Resultsmentioning
confidence: 99%
“…The Ovarian Tumor Tissue Consortium (OTTA) includes tissue-based studies and focuses on tumor biomarkers and survival [106,107], with several large efforts underway. Compilations of systematically harmonized public gene expression datasets such as curatedOvarianData [108] are complementary resources. Although these consortia and compendia represent large numbers of studies, analyses of the rarer histotypes, MC, LGSC, and CCC, remain underpowered.…”
Section: Challenges and Limitations In Studying Epidemiology Of Cancementioning
confidence: 99%